Nutritional Interventions for Treating Cancer-Related Fatigue: A Qualitative Review. (2nd January 2019) - Inglis, Julia E.; Lin, Po-Ju; Kerns, Sarah L.; Kleckner, Ian R.; Kleckner, Amber S.; Castillo, Daniel A.; Mustian, Karen M.; Peppone, Luke J.
Abstract: Cancer-related fatigue (CRF) is a debilitating syndrome that persists for many cancer survivors for years after treatment. Symptoms include early and persistent fatigue, functional decline, depression, and cognitive difficulties. Inflammation, assessed using pro-inflammatory biomarkers, is increased in cancer survivors with fatigue and treatments for fatigue are often aimed at reducing inflammation. Additionally, cancer and its treatment lead to nutritional complications, changes in body composition, and nutritional deficiencies that potentially weaken the cancer survivor and impact CRF. We conducted a qualitative review of clinical trials that assessed nutritional interventions for preventing and treating CRF. Further studies were examined that used nutritional interventions to address inflammation and fatigue, due to the dearth of nutrition research directly related to CRF. Dietary intake prior to, during, and after cancer treatment appears to affect fatigue levels. Increased protein intake may help preserve lean mass and body composition. Dietary patterns that reduce inflammation, such as the Mediterranean diet and other plant-based diets, appear tolerable to cancer survivors and may reduce fatigue. Supplementation with ginseng, ginger, or probiotics may improve cancer survivors' energy levels. Nutritional interventions, alone or in combination with other interventions should be considered as therapy for fatigue in cancer survivors.